1995
DOI: 10.1007/bf01726532
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic control of the heart and peripheral vessels in human septic shock

Abstract: Reduced LF components of the variability of cardiovascular signals are characteristic of septic shock, confirming the presence of abnormal autonomic control. Restored sympathetic (LF) modulation seems to be associated with a favourable prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 29 publications
4
46
1
4
Order By: Relevance
“…In the present study, LFnu was correlated with both APACHE II [r = Ϫ0.67, (95% CI = Ϫ0.88 to Ϫ0.22), r 2 = 0.45] and SOFA scores [r = Ϫ0.80 (95% CI = Ϫ0.93 to Ϫ0.46), r 2 = 0.64]. While our confidence intervals are wide, these findings are similar to those of Garrard et al 31 and Piepoli et al, 28 who reported similar r-values of Ϫ0.66 and Ϫ0.58, respectively, in their comparisons of LFnu with APACHE II.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the present study, LFnu was correlated with both APACHE II [r = Ϫ0.67, (95% CI = Ϫ0.88 to Ϫ0.22), r 2 = 0.45] and SOFA scores [r = Ϫ0.80 (95% CI = Ϫ0.93 to Ϫ0.46), r 2 = 0.64]. While our confidence intervals are wide, these findings are similar to those of Garrard et al 31 and Piepoli et al, 28 who reported similar r-values of Ϫ0.66 and Ϫ0.58, respectively, in their comparisons of LFnu with APACHE II.…”
Section: Discussionsupporting
confidence: 88%
“…However, this limitation was intrinsic to our study design, since our goal was to examine the ability of HRV analysis to identify patients at risk for deterioration from a population of moderately ill ED patients. It is note- worthy that the degree of correlation between APACHE II and LFnu was similar to the results reported by Garrard et al 31 and Piepoli et al 28 in their studies of a ''sicker'' population [Garrard: mean APACHE II = 23 (range 6-41); Piepoli: mean APACHE II = 25 (range 19-31); our study: mean = 14 (range ].…”
Section: Limitationssupporting
confidence: 90%
See 2 more Smart Citations
“…Last, the results of our study suggest that caution should be exercised in the inter- pretation of studies on autonomic control in critically ill patients who receive intravenous inotropes. 26 Dobutamine had similar effects on LF and HF variability of the RR interval. RR interval variability normally results from the complex interactions of phasic changes in sympathetic and vagal drive to the sinus node.…”
Section: Discussionmentioning
confidence: 93%